DIE UNIFORM KNOPE VAN DIE SUID-AFRIKAANSE VLOOT EN SY VOORGANGERS - Bisset, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
No article has previously been written on the buttons of the SA Navy and its predecessors. As a complete history of these buttons will necessitate interviews with a considerable number of pensioned naval personnel and the sources of the SADF Archives will first have, to be consulted, Lt Cdr Bisset has in the mean time submitted this intermediary report, together with very interesting photographic material on the subject. More detailed information on th'e buttons of the SA Navy and its predecessors that readers may wish to offer, will be most welcome.